2014
DOI: 10.1093/gji/ggu450
|View full text |Cite
|
Sign up to set email alerts
|

Source-independent full wavefield converted-phase elastic migration velocity analysis

Abstract: S U M M A R YConverted phase (CP) elastic seismic signals are comparable in amplitude to the primary signals recorded at large offsets and have the potential to be used in seismic imaging and velocity analysis. We present an approach for CP elastic wave equation velocity analysis that does not use source information and is applicable to surface-seismic, microseismic, teleseismic and vertical seismic profile (VSP) studies. Our approach is based on the crosscorrelation between reflected or transmitted PP and CP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…However, we found that the deconvolutional SICW-IC with S-wave illumination is less sensitive to S-wave uncertainty than the other three SICW-ICs, and when the V P ∕V S is preserved, the image degradation is less severe (Figure 10f). Shabelansky et al (2015b) present an approach based on the SICW-IC for P-and S-wave speed reconstruction. This method is based on the crosscorrelational form; wave-speed updating based on the deconvolutional forms is a subject of future research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we found that the deconvolutional SICW-IC with S-wave illumination is less sensitive to S-wave uncertainty than the other three SICW-ICs, and when the V P ∕V S is preserved, the image degradation is less severe (Figure 10f). Shabelansky et al (2015b) present an approach based on the SICW-IC for P-and S-wave speed reconstruction. This method is based on the crosscorrelational form; wave-speed updating based on the deconvolutional forms is a subject of future research.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, we have developed a wave speed estimation approach for use with SICW imaging that allows one to find reliable wave speed models and thus obtain improved images (Shabelansky et al, 2015b). To highlight the sensitivity of SICW-ICs to wave speed variations, we present two sets of imaging results; first with severely smoothed wave speed models and second with a smooth elliptical inclusion at the center of the S-wave speed model.…”
Section: Marmousi Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2‐D Sigsbee2b model test showed that the reverse‐time imaging method can reveal scatterers in the subsurface. Shabelansky () applied the reverse‐time imaging method and used the coherence between back‐propagating P and S wavefields to image the discontinuous structures in the Hengill geothermal area. Similar concepts have also been applied to teleseismic waveforms to image the Moho discontinuity (Shang et al, , ).…”
Section: Introductionmentioning
confidence: 99%
“…To map the Moho discontinuity, Shang et al (2012) presented an imaging condition of cross-correlating P and S wavefields after wavefield decomposition during elastic wave propagation of the teleseismic data. Following the same idea, Shabelansky et al (2015) developed a velocity analysis method using reflection/transmission waves and converted waves using both active and passive seismic data. Shabelansky et al (2017) further elaborated the source-independent converted wave imaging condition for better amplitude balancing with the deconvolutional forms.…”
Section: Introductionmentioning
confidence: 99%